An investigation of ultrasonic nanocrystal surface modification machining process by numerical simulation. (May 2015) - Wu, Bo; Zhang, Linjie; Zhang, Jianxun; Murakami, Ri-ichi; Pyoun, Young-Shik
Highlights: A simplified model of UNSM was developed by equivalent static loading method. A 3-D model was built to investigate the machining process of UNSM. Small and stable energy dissipation of UNSM process can be found. Lower machining linear velocity can produce severe surface work hardening. Static loading has a greater impact to UNSM result comparing others. Abstract: As a method for surface severe plastic deformation (S 2 PD), ultrasonic nanocrystal surface modification (UNSM) enhances metal surface properties through striker peening, a metal dimpling process driven by ultrasonic vibration energy. UNSM treatment introduces residual stress, surface hardening, and nano-crystalline structures into metal surfaces which are beneficial for reducing wear, fatigue, and corrosion properties. In this paper, the process of UNSM is described and a simplified physical model created using the equivalent static loading method is presented. Along with the simplified physical model, a finite elements simulation model was developed. Effective plastic strain was considered as a parameter for evaluating the level of work hardening produced in the simulation. The dynamic processes and energy dissipation were also examined, and it was found that different kinds of energy dissipation occur during UNSM treatment. Comparisons between the processing parameters (processing velocity, static load, and feed rate) were performed using a simulated example of UNSM linear processing. The results show that the linear processing produces a uniform region containing identical distributions of residual stress and effective plastic strain. The effects of the parameters on the processing results (residual stress, plastic deformation and work hardening) were likewise studied using UNSM linear processing. Compared to processing velocity, a high static load produced more work hardening and higher compressive residual stress. Surface deformation and residual stress results were also more sensitive to static load than processing velocity. Feed rate was found to be an important parameter as well, greatly influencing both surface deformation and work hardening.